Contract-based secure and resilient control for industrial cyber-physical systems - Maria Mustafa Doola (Nanyang Technological University, 2020)
Smart manufacturing has transformed manufacturing industries to increasingly depend on the computing power of cyber-physical systems. These cyber-physical systems are designed to control manufacturing processes and take appropriate decisions without human intervention. Though this movement towards technology has drastically improved productivity, smart manufacturing has opened the doors to a different landscape of threats which depend on exploiting the vulnerabilities of a cyber infrastructure. In a cyber-physical system, the physical plant takes appropriate decisions based on the data that is transmitted via its cyber-infrastructure. Hence, it is extremely important to maintain data integrity of the cyber-infrastructure to keep the system secure and resilient to cyber-attacks. This will ensure safe operation of the system’s components. In this project, a Fischertechnik Sorting Line with Color Detection training model is used as our cyber-physical system framework. This project focusses on implementing security measures that ensure the security of the Fischertechnik Model, in particular, the integrity of the color sensor value, which determines the behavior of the Fischertechnik Model to sort a colored token into its designated storage bin according to the color of the token. Advanced Encryption Standard (AES) has been implemented in this project to encrypt and decrypt the color sensor data on the Fischertechnik Model. We have designed an AES encryption program on the Arduino Uno and an AES decryption program on the Raspberry Pi 3. The data communication between the Arduino Uno and the Raspberry Pi 3 implements Universal Asynchronous Reception/Transmission (UART) serial communication. Additionally, we have also conducted experiments on the three different key length variations of AES (128-bits, 192-bits and 256-bits) to analyze the time performance and memory consumption for each of these key lengths when implemented on the Fischertechnik Model.